Justification of the financing schedule for an enterprise's innovative project using dynamic programming. Issue 3 (November 2020) - Eremeev, D V; Stupina, A A; Kukartsev, V V; Tynchenko, V S; Leonteva, A A; Pavlenko, A A
Abstract: Get additional profit, increase the profitability of sales, reduce costs - the main goals of any enterprise. To achieve these goals, it is necessary to constantly analyze the available opportunities both in current activities and when investing. The article considers one of the methods for optimizing the investment program by finding the best option for the ratio of cost and time of own and borrowed sources of financing for an investment project. Various forms are considered as additional sources of capital: budget financing, issuing a bonded loan, a credit line, loans from various banking institutions. The results obtained allow us to make balanced management decisions about the structure of project financing. The final data is used to form the overall financial plan.